Pembinaan Literasi Dasar Melalui Self Motivation Untuk Mengembangkan Softskill Guru SD - Awalina Barokah; Sarwo Edy; Septian Mukhlis; Muhammad Faiz Rayan (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Teachers are central to making learning successful. The skills possessed by the teacher determine the learning that takes place in the classroom. These skills are not only hard skills that teachers must possess, but also soft skills. Basic literacy will be a means to develop teachers' soft skills in managing learning in the classroom. This community service aims to provide teachers with an understanding of the basic literacy skills that teachers possess through self-motivation. In SDN 02 Bojongmenteng, Leuwidamar, Lebak Regency, Banten Province, this community service was conducted for 10 teachers. The flow of community service begins with planning, licensing, workshops, mentoring, support, evaluation and reflection. There is a significant increase in basic literacy and soft skills development, especially in digital literacy, communication, classroom management and character development. Teacher-owned self-motivation is not just motivation, but structured and sustained self-motivation mentoring.